Cholangiocarcinoma with a Background of Hepatitis B Virus-associated Cirrhosis - Takegoshi, Kunio; Bannasch, Peter (Internal medicine, 2001)
Japan's largest platform for academic e-journals: J-STAGE is a full text database for reviewed academic papers published by Japanese societies
Gesehen am 08.02.2019